2012
DOI: 10.1073/pnas.1208280109
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax toxin protective antigen integrates poly-γ- d -glutamate and pH signals to sense the optimal environment for channel formation

Abstract: Many toxins assemble into oligomers on the surface of cells. Local chemical cues signal and trigger critical rearrangements of the oligomer, inducing the formation of a membrane-fused or channel state. Bacillus anthracis secretes two virulence factors: a tripartite toxin and a poly-γ-D-glutamic acid capsule (γ-DPGA). The toxin's channel-forming component, protective antigen (PA), oligomerizes to create a prechannel that forms toxic complexes upon binding the two other enzyme components, lethal factor (LF) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Capsule components shed during infection can be found in circulation and may function to activate the complement cascade at sites remote from infection disrupting the chemoattractant gradient (Makino et al ., ). Circulating capsule may also increase the efficiency of cellular intoxication by stabilizing intracellular PA pore formation (Kintzer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Capsule components shed during infection can be found in circulation and may function to activate the complement cascade at sites remote from infection disrupting the chemoattractant gradient (Makino et al ., ). Circulating capsule may also increase the efficiency of cellular intoxication by stabilizing intracellular PA pore formation (Kintzer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the availability of two end-state structures for wild type (WT) PA prepore and pore (Jiang et al, 2015;, the extreme differences in their organization and molecular interactions has make it challenging to rationalize the sequential steps that are involved in the maturation process. Significant structural differences between the two end states include the formation of a 105 Å membrane-spanning channel, the nearly complete (Kintzer et al, 2012). (B) 2D schematic of the secondary structure organization of domain 2 (segment V262-N458) in the prepore (red dash box) and the pore (green dash box) states.…”
Section: Biochemical Analysis Of D425a Heptamer Identifies Reversiblementioning
confidence: 99%
“…10−14 Studies have revealed that each PA63 monomer of the prepore binds a receptor through two domains. Interaction of PA domain 4 with the receptor is retained throughout the conversion process, whereas domain 2 contacts are lost.…”
mentioning
confidence: 99%